Risk factors for dysplastic lesions in the proximal stomach in patients with familial adenomatous polyposis - Bouchiba, Hicham; Aelvoet, Arthur S.; Bastiaansen, Barbara A.J.; Bossuyt, Patrick M.M.; Dekker, Evelien (Endoscopy International Open, 2025)
Gastric cancer is a recently recognized challenge in management of familial adenomatous polyposis (FAP), mostly developing in the proximal stomach amid carpeting fundic gland polyposis. Dysplastic lesions in the proximal stomach might be the precursor lesions for gastric cancer in FAP. We aimed to describe incidence of dysplastic lesions in the proximal stomach and to identify risk factors for these dysplastic lesions.Data were collected from FAP patients who had undergone esophagogastroduodenoscopy (EGD) between 2015 and 2023 at our academic center. To identify putative risk factors for dysplastic lesions in the proximal stomach, we used multivariable Cox proportional hazard regression modeling.Among the 196 FAP patients who underwent EGD at our center, 33 (17%) were diagnosed with dysplastic lesions in the proximal stomach. In total 61% were female and median age at diagnosis was 49 years (range 19–80). A total of 105 dysplastic lesions were identified. Ten (9.5%) showed high-grade dysplasia. During the study period, seven patients were diagnosed with gastric cancer. Carpeting fundic gland polyposis (≥ 100 polyps) (hazard ratio [HR] 8.94; P < 0.001), biliary reflux (HR 1.92; P = 0.017), and proton pump inhibitors (HR 1.78; P = 0.014) were significant predictors of dysplastic lesions in the proximal stomach. Advanced Spigelman stage (III/IV) (HR 0.37; P < 0.001) was associated with a significantly lower risk.Carpeting fundic gland polyposis, biliary reflux, and use of PPIs were identified as putative risk factors for dysplastic lesions in the proximal stomach. Presence of these risk factors should alert endoscopists to assess the stomach more thoroughly.
Keywords: Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopy Lower GI Tract; Polyps / adenomas / ...